A hybrid security policy for Europe: Resilience, deterrence, and defense as leitmotifs - Claudia Major; Christian Mölling (Stiftung Wissenschaft und Politik (SWP), 2015)
Under the term "hybrid warfare" the different methods with which Russia destabilizes Ukraine are discussed, be it propaganda or the infiltration of society. However, the problems that NATO and EU states face in dealing with hybrid threats go far beyond the Ukraine conflict - they point to systematic vulnerabilities of Western societies. This greater spectrum of risks disappears from view, because the current debate is focused on the conflict with Russia and its military dimension. The next conflict may already not follow the Ukrainian pattern. Therefore, EU and NATO must place systematic vulnerabilities at the center of a hybrid security policy, which should build upon a reorganized relationship of resilience, deterrence, and defense. (SWP Comments)
Keywords: 320